Heterozygous DHTKD1 variants in two European cohorts of amyotrophic lateral sclerosis patients - Osmanovic, Alma; Gogol, Isabel; Martens, Helge; Widjaja, Maylin; Müller, Kathrin; Schreiber-Katz, Olivia; Feuerhake, Friedrich; Langhans, Claus-Dieter; Schmidt, Gunnar; Andersen, Peter M.; Ludolph, Albert C.; Weishaupt, Jochen H.; et al. (Genes, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by progressive upper and lower motor neuron (LMN) loss. As ALS and other neurodegenerative diseases share genetic risk factors, we performed whole-exome sequencing in ALS patients focusing our analysis on genes implicated in neurodegeneration. Thus, variants in the DHTKD1 gene encoding dehydrogenase E1 and transketolase domain containing 1 previously linked to 2-aminoadipic and 2-oxoadipic aciduria, Charcot-Marie-Tooth (CMT) disease type 2, and spinal muscular atrophy (SMA) were identified. In two independent European ALS cohorts (n = 643 cases), 10 sporadic cases of 225 (4.4%) predominantly sporadic patients of cohort 1, and 12 familial ALS patients of 418 (2.9%) ALS families of cohort 2 harbored 14 different rare heterozygous DHTKD1 variants predicted to be deleterious. Four DHTKD1 variants were previously described pathogenic variants, seven were recurrent, and eight were located in the E1_dh dehydrogenase domain. Nonsense variants located in the E1_dh domain were significantly more prevalent in ALS patients versus controls. The phenotype of ALS patients carrying DHTKD1 variants partially overlapped with CMT and SMA by presence of sensory impairment and a higher frequency of LMN-predominant cases. Our results argue towards rare heterozygous DHTKD1 variants as potential contributors to ALS phenotype and, possibly, pathogenesis.
Gesehen am 15.11.2022
Published: 29 December 2021